Review of compounds that exhibit radioprotective and/or mitigatory effects after application of diagnostic or therapeutic ionizing radiation. (3rd April 2023) - Zivkovic Radojevic, Marija; Milosavljevic, Neda; Miladinovic, Tatjana B.; Janković, Slobodan; Folic, Marko
Abstract: Purpose: Exposure to ionizing radiation can be accidental or for medical purposes. Analyzes of the frequency of radiation damage in the general population, it has been determined that by far the most common are those that occur as a result of diagnostic or therapeutic procedures. Damage caused by radiation, either accidentally or for therapeutic purposes, can be reduced by the use of radioprotectors, mitigators or other therapeutic agents. A detailed research of the available literature shows that there is little systematized data of potentially radioprotective and/or mitigating effects of drugs from the personal therapy of patients during the application of therapeutic ionizing radiation. The aim of this paper is to present review of compounds, especially personal therapy drugs, that exhibit radioprotective and/or mitigating effects after the application of diagnostic or therapeutic ionizing radiation. Conclusions: Given the widespread use of ionizing radiation for diagnostic and therapeutic purposes, there is a clear need to create a strategy and recommendations of relevant institutions for the use of radioprotectors and mitigators in everyday clinical practice, with individual evaluation of the patient's condition and selection of the compounds that will show the greatest benefit in terms of radioprotection.